Respuesta :
Answer:
Step-by-step explanation:
So let’s set up equations.
X-y=9
X+2y=27
Now, we can use elimination by taking the first equation away from the second.
3y=18
Y=6
Since y=6, then x=15.
Answer: 15 and 6
Step-by-step explanation:
Okay, so to solve this we will call one number x and the other number y.
so x-y=9
and x + 2y = 27
so we can turn x-y=9 into x=y+9
and plug the (y+9) into the second equation
so (y+9) + 2y = 27
3y = 18
y = 6
then we can go back and plug 6 in for y in the first equation
x - 6 = 9
x = 15
so x = 15 and y = 6